PHYTOREMEDIAL ROLE OF WITHANIA SOMNIFERA EXTRACT ON BIOCHEMICAL PARAMETERS IN LIVER OF EPINEPHRINE INDUCED STRESSED ALBINO MICE - SHIV SHANKER KUMAR; BHASKAR SHARMA; MOHAMMAD SUHAIL (International Journal of Pharma and Bio Sciences, 2013)
During our present study, we examined the W. somnifera extract effect on epinephrine induced stress. Forty Swiss albino mice were divided into three groups as non stressed group and stressed group and extract treated group .The stressed groups were exposed to 2 weeks and 4 weeks of chronic immobilization stress with epinephrine. At the end of the 2 and 4 weeks the mice were sacrificed and blood samples were collected through orbital sinus method. The blood samples of these groups were analyzed for selected biochemical parameters viz. Serum Glutamate Oxaloacetate Transaminase (SGOT), Serum Glutamate Pyruvate Transaminase (SGPT), and Bilirubin which were found to be significantly increased in the stressed group when compared to the non stressed Control. The present data indicate that epinephrine induced stress causes the significant alterations in the SGOT, SGPT and Bilirubin levels affecting the normal metabolism in liver. These elevations were found to be significantly reversed in W. somnifera extract treated group. Our findings have relevance as human beings are exposed to several stressors in routine life.